Glazed Pottery Throughout the Middle and Modern Ages in Northern Spain - Ainhoa Alonso-Olazabal; Juan Antonio Quirós Castillo; Maria Cruz Zuluaga; Luis Ángel Ortega (Heritage)
A total of forty samples of medieval and modern glazed pottery from northern Spain were studied. Chemical and microstructural analyses of the glazes were performed by scanning electron microscopy coupled with electron dispersive spectroscopy (SEM-EDX), while the chemical composition of the pottery bodies and slips were determined by X-ray Fluorescence (XRF). The glazes studied come from the Santa Barbara Hill site (Tudela), the Treviño Castle site (Treviño), the Vega workshop (Burgos) and the Torrentejo village (Labastida) and correspond to transparent glazes and opaque white glazes. Transparent glazes were lead glazes with variable PbO content. Opaque white glazes were lead-tin and lead–alkaline–tin glazes. The glaze was mainly applied to a pre-fired body made of local clays, but the glazes of the Santa Barbara Hills pottery (Tudela) were applied to raw bodies. The microstructure of the interfaces indicates a single firing process for the glazed pottery from Tudela and a double firing process in the rest of the sites. Some correlation are identified between the use of specific clays to produce different glaze colours. White opaque glazes are applied to calcium-rich clays. Similarly, calcium-rich clays were used to produce dark green transparent glazes, while clays and slips aluminium–rich were used to produce light green and light honey glazes. Iron was also identified as the main colouring agent, although copper was also used. The white glazes were opacified by the addition of cassiterite and sometimes quartz and feldspar. The glazed pottery was mainly of local origin, but the identification of some non-local pottery at all sites suggests a pottery trade.